On the combined role of the astrophysical force limit and Avogadro number in final unification - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2014)
Magnitude of the unified force can be assumed to be equal to the classical or astrophysical force limit . Strength of any interaction can be defined as the ratio of the operating force magnitude and the magnitude of . Let the gravitational interaction taking place at black holes be called as ‘Schwarzschild interaction’. If strength of Schwarzschild interaction is unity, then weak interaction strength seems to be times less than the Schwarzschild interaction and strong interaction strength seems to be times less than the Schwarzschild interaction. Based on these concepts and considering the Avogadro number as an absolute and discrete number, basics of final unification can be understood.